Environmental impact of FDI – the case of US subsidiaries. Issue 3 (16th September 2019) - Cerdeira Bento, João Paulo; Moreira, António
Abstract : Purpose: This paper aims to examine how foreign direct investment (FDI) and firm-specific advantages (FSAs) of US multinational enterprises (MNEs) majority-owned subsidiaries affect environmental pollution in host countries. The research results contribute to helping managers and policymakers understand the environmental impact of MNEs activities, and encourage these firms to develop environmentally responsible management (ERM) as an element of their corporate social responsibility practice. Design/methodology/approach: Panel data consisting of developing and developed countries spanning the years 2004 through 2014 are used. The dynamic panel generalised method of moments technique is implemented. This method avoids common estimation bias, such as endogeneity, heteroscedasticity and autocorrelation. Findings: This paper finds that the direct environmental impacts of FDI vary significantly between the two groups of countries. The environmental benefits of FDI to the recipient country are achieved through capital and technology transfer. The study also reveals that R&D intensity moderates the relationship between FDI and environmental pollution in both developing and developed countries in such a way that environmental pollution decreases. Research limitations/implications: Future research could explore the environmental impact of MNEs on host countries by considering both equity and non-equity entry modes. The findings offer some support to host government policies offering generous incentive packages to attract R&D investment to improve environmental pollution. This research raises questions as to the reasons corporations operating in developing and developed countries should pursue their ERM practices. Originality/value: This research examines both the direct effect of FDI and the moderating effects of FSAs on the relationship between FDI and the environment. Although previous studies have already looked at the relationship between FDI and the environment, the moderating effect of FSAs is very under-developed in this relationship.